Evaluation of RANTES analogue expression in Nicotiana benthamiana and Lycopersicon esculentum and their topical microbicidal activity - Eloff, Jacobus Nicolaas (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.